Impedance planimetry values for predicting clinical response following peroral endoscopic myotomy - Moran, Robert A.; Brewer Gutierrez, Olaya I.; Rahden, Burkhard; Chang, Kenneth; Ujiki, Michael; Yoo, In Kyung; Gulati, Shraddha; Romanelli, John; Al-Nasser, Mohammed; Shimizu, Toshitaka; Hedberg, Mason H.; Cho, Joo Young; Hayee, Bu; Desilets, David; Filser, Jörg; Fortinsky, Kyle; Haji, Amyn; Fayad, Lea; Sanaei, Omid; Dbouk, Mohamad; Kumbhari, Vivek; Wolf, Bethany J.; Elmunzer, B. Joseph; Khashab, Mouen A. (Endoscopy, 2020)
Background There is growing interest in developing impedance planimetry as a tool to enhance the clinical outcomes for endoscopic and surgical management of achalasia. The primary aim of this study was to determine whether impedance planimetry measurements can predict clinical response and reflux following peroral endoscopic myotomy (POEM). Methods A multicenter cohort study of patients with achalasia undergoing POEM was established from prospective databases and retrospective chart reviews. Patients who underwent impedance planimetry before and after POEM were included. Clinical response was defined as an Eckardt score of ≤ 3. Tenfold cross-validated area under curve (AUC) values were established for the different impedance planimetry measurements associated with clinical response and reflux development. Results Of the 290 patients included, 91.7 % (266/290) had a clinical response and 39.4 % (108/274) developed reflux following POEM. The most predictive impedance planimetry measurements for a clinical response were: percent change in cross-sectional area (%ΔCSA) and percent change in distensibility index (%ΔDI), with AUCs of 0.75 and 0.73, respectively. Optimal cutoff values for %ΔCSA and %ΔDI to determine a clinical response were a change of 360 % and 272 %, respectively. Impedance planimetry values were much poorer at predicting post-POEM reflux, with AUCs ranging from 0.40 to 0.62.Conclusion Percent change in CSA and distensibility index were the most predictive measures of a clinical response, with a moderate predictive ability. Impedance planimetry values for predicting reflux following POEM showed weak predictive capacity.